Management of Cash Flows - Senkus, Kastytis (Ekonomika, 2004)
Consistent management of cash flows, predetermining the results of the Company’s activities, serves as one of the most important priorities of management of the Company. However, very little attention bas been devoted to this problem both in literature and in practical activities. The following functions of management of cash flows have been singled out and investigated: planning, organization, forecasting and administration. These functions are closely interrelated and stipulate each other.It has been proved that the process of management of cash flows should be executed consistently, i.e. per stages. The following stages of management of cash flows have been singled out: accumulation of the information on cash flows, analysis of cash flows for the previous and current period under review, forecasting of cash flows, decision taking on management of cash flows, decision implementation on management of cash flows.The following most important spheres of management of cash flows have been singled out, i.e. management of the cash in-flow, management of pays out, keeping of the optimal money level, issue of the monetary budgets and forecasts, investment of the cash surplus.It’s important to take care of irreproachable registration of the documents on cash circulation (inflows and pays out) and cash rests as the cash produces the direct impact on indices of financial accounts. It’s necessary to block the way to losses through misuse and thefts, not to lend the cash funds without img sure about the possibilities of their return, not to keep large cash amounts, which do not create the income, at the bank accounts. Each company should have as much money as would be enough to settle up with its creditors after expiry of the payment term. The opposite situation may cause bankruptcy.